Long-term effects of the antibacterial agent triclosan on marine periphyton communities - Eriksson, Martin; Johansson, Henrik; Fihlman, Viktor; Grehn, Alexander; Sanli, Kemal; Andersson, Mats X; Blanck, Hans; Arrhenius, Åsa; Sircar, Triranta; Backhaus, Thomas (PeerJ PrePrints, 2014)
Triclosan (TCS) is a widely used antibacterial agent that has become a ubiquitous contaminant in freshwater, estuary and marine environments. Concerns for potential adverse effects of TCS have been described in several recent risk assessments. Effects on freshwater microbial communities have been quite well studied but studies addressing effects on marine microbial communities are scarce. Here we describe short- and long-term effects of TCS on marine periphyton (microbial biofilm) communities. Short-term effects on photosynthesis were estimated after 60 – 210 minutes exposure. Long-term effects on photosynthesis, chlorophyll fluorescence, pigment content, community tolerance and bacterial carbon utilization were studied after exposing periphyton for 17 days in flow-through microcosms to 0.316 - 10 000 nM TCS. Results from the short-term studies show that TCS is toxic to periphyton photosynthesis. EC50 values of 1080 and 3000 nM were estimated using 14CO2-incorporation and Pulse Amplitude Modulation (PAM), respectively. After long-term TCS exposure in flow-through microcosms photosynthesis estimated using PAM was, however, not inhibited by TCS concentrations up to 1000 nM, but instead increased with increasing TCS concentration. Similarly, the amount of photosynthetic pigments increased after an exposure of 31.6 nM TCS and higher; at 316 nM TCS the pigment amounts reached between 140 and 190% of the control level. Pollution-Induced Community Tolerance (PICT) was observed for algae and cyanobacteria at 100 nM TCS and higher. In spite of the widespread use of TCS as an antibacterial agent, the compound did not have any effects on bacterial carbon utilization after long-term exposure.
Keywords: personal care products; Pollution-Induced Community Tolerance (PICT); microbial toxicology; irgasan; mode of action; biofilm